KONSEP SAKINAH DALAM RUMAH TANGGA PERSPEKTIF AL-RAZI DAN ABRAHAM MASLOW - Ahmad Daniyal; Zainul Muin Husni (Hakam: Jurnal Kajian Hukum Islam dan Hukum Ekonomi Islam)
Peace in the family (sakinah) is the hope of all couples. Creating a sakinah family is not merely the duty of a wife, but must be supported by both parties (husband and wife). Household life will also require several patterns that form the basis of a strong and harmonious family foundation. This pattern will later complement the deficiencies that should exist in the family. During the trip, many families in which there are problems, which are caused by several unfulfilled needs, instead take the way of divorce rather than maintaining family relationships.